Assessing the association between smoking and hypertension: Smoking status, type of tobacco products, and interaction with alcohol consumption - Gao, Ningxin; Liu, Tao; Wang, Yawen; Chen, Min; Yu, Lisha; Fu, Chaowei; Xu, Kelin (Frontiers in Cardiovascular Medicine, 2023)
Background: The association between tobacco use and hypertension risk has been extensively researched but remains controversial, and few existing studies have considered the role of tobacco type and dosage response in this association. In this context, this study aims to provide epidemiological evidence for the possible relationship between tobacco smoking and future hypertension risk, with the tobacco type and consumption dose into consideration. Methods: This study was based on 10-year follow-up data from the Guizhou Population Health Cohort conducted in southwest China. Multivariate Cox proportional hazards regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (95%CIs), and restricted cubic spline analyses were performed to visualize the dose-response association. Results: 5625 participants (2563 males and 3062 females) were included in the final analysis. Heavy smokers of machine-rolled cigarettes had an elevated hypertension risk compared with nonsmokers (HR: 1.50, 95% CI: 1.05-2.16). The interaction effects of heavy smoking-heavy drinking patterns increased the future hypertension risk, with an adjusted HR of 2.58 (95% CI: 1.06-6.33). Conclusions: This study did not find a significant association between overall tobacco use status and the risk of hypertension. However, heavy machine-rolled cigarette smokers had a statistically significant increased risk of hypertension compared with nonsmokers, and a J-shape association has been found between the average daily consumption of machine-rolled cigarettes and the risk of hypertension. Besides, tobacco and alcohol consumption jointly increased the long-term hypertension risk